Why CRM Doesn't Work - Newell, Fredrick; Newell, Fredrick (Bloomberg Press, 2003)
CRM was supposed to help businesses better understand their customers and increase efficiency. Yet most companies are not getting the return they expected. Is it possible to make customers happy and, at the same time, improve ROI? Is there a practical, affordable way to get customers to say what they really want? In Why CRM Doesn't Work, leading international marketing consultant Frederick Newell explains why it's time to change the game to CMR (Customer Management of Relationships). CMR allows companies to empower customers so they'll reveal what kind of information they want, what level of service they want to receive, and how to communicate with them--where, when, and how often. It is a bold solution for businesspeople at all levels in all industries who want to stay ahead of the curve in the development of customer loyalty. Newell shows by lesson and example why the current CRM isn't working, what needs to change, and how to put the CMR philosophy to work--without additional expense. The book includes case studies of good and bad relationship marketing from companies as diverse as Kraft Foods, Procter & Gamble, Budweiser, Charles Schwab, Dell, IBM, Lands' End, Sports Authority, Radio Shack, and Staples. With the knowledge in this book, a company can learn to build long-term relationships and bring in profits instead of relying on one-time sales. Why CRM Doesn't Work is important reading for companies of every size that are trying to satisfy and sell to today's consumer.